Foot and ankle characteristics associated with fear of falling and mobility in community‐dwelling older people: a cross‐sectional study - Fateme Pol; Zahra Khajooei; Sayed Mohsen Hosseini; Alireza Taheri; Saeed Forghany; Hylton B. Menz (Journal of Foot and Ankle Research, 2022)
Abstract Background Fear of falling is multifactorial in etiology and is associated with falls. It has been demonstrated that foot problems increase the risk of falls in older people. Therefore, the objective of this study was to investigate the associations of foot and ankle characteristics with fear of falling and mobility in community‐dwelling older people. Method One hundred and eighty‐seven community‐dwelling older adults (106 females) aged 62–90 years (mean 70.5 ± 5.2) from Isfahan, Iran, were recruited. Foot and ankle characteristics (including foot posture, range of motion, muscle strength, deformity, tactile sensation, pain and dynamic function), fear of falling (Fall Efficacy Scale International) and mobility (Timed Up and Go Test) were measured. Two multivariate linear regression analyses identified variables independently associated with fear of falling and mobility. Results Linear regression analysis revealed that less ankle plantarflexor muscle strength, greater pressure‐time integral, foot pain, and reduced tactile sensitivity of the ankle were significantly and independently associated with increased fear of falling. The total variance explained by the model was 59%. Less ankle plantarflexor muscle strength, greater pressure‐time integral, and slower centre of pressure velocity were significantly and independently associated with poorer mobility. The total variance explained by the model was 48%. Conclusion Several foot and ankle characteristics are associated with fear of falling and mobility in older people. Targeting these modifiable risk factors may play a role in reducing fear of falling and enhancing mobility performance in this population.